Fecal Sludge Management in Low Income Settlements: Case Study of Nakuru, Kenya - Simiyu, Sheillah; Chumo, Ivy; Mberu, Blessing (Frontiers in Public Health, 2021)
Introduction: In order to meet the sustainable development goals targets of sanitation, countries aim to increase access to safely managed sanitation services for its citizens. Safely managed sanitation services refers to improved sanitation technologies that are not shared with other households and where excreta is treated and disposed; or stored, transported and treated off-site. In most Sub-Saharan Africa (SSA) countries, on-site sanitation facilities such as latrines and septic tanks are common, with low-income urban settlements mainly using pit latrines. However, little is documented about the management of sludge from these facilities, especially in low income settlements in secondary and emerging cities. This lack of data is a major hindrance to public health, development and planning efforts by governments and planning agencies. This study specifically assesses practices and challenges along the sanitation value chain related to containment, emptying, transportation, treatment and recycling of fecal sludge. Methods: The study was carried out in low income settlements in Nakuru, a secondary city in Kenya. Over half the population in Nakuru live in low income areas and majority of these residents use pit latrines. A case study design was selected for this study and data was collected using qualitative methods. Data was collected through In-depth interviews and Focus Group Discussions using in depth interview guide and focus group discussion guides that had questions on sanitation practices along the value chain, challenges, opportunities available, and recommendations for improvement. Analysis was done through content analysis by reading the transcripts multiple times to gain a sense of the flow of the discussion. Thereafter, coding was done by following emergent issues and thereafter categories were identified which formed the basis for providing a picture of FWM practices in the settlements. Results: On site sanitation facilities are dominant in the settlements, but they are few and are shared by several households. These facilities were unclean, and they filled up at a fast rate because of the high number of users. The latrines were emptied by manual emptiers who used mechanized equipment but complemented with manual emptying using buckets. Sludge was transported to a central collection point using large and small scale means of transportation, before transfer to the treatment site for final treatment and disposal. Various stakeholders are involved in capacity building of emptiers as well as in the transportation, treatment and disposal of fecal sludge in the settlements. Challenges along the stages of the value chain included negative community perceptions and attitudes toward fecal sludge management. Conclusion: The results highlight the need to address the challenges along the chain by involvement of state and non-state actors. Low income areas have high populations and thus contribute huge amounts of fecal sludge. Deliberate efforts to consolidate such data from low income areas will result in availability of data, and informed decision making for stakeholders at national and international levels.